Synthesis and Characterization of peri-Heptacene on a Metallic Surface - Biswas, Kalyan; Urgel, Jose I.; Ajayakumar, M. R.; Ma, Ji; Sanchez-Grande, Ana; Edalatmanesh, Shayan; Lauwaet, Koen; Mutombo, Pingo; Gallego, Jose M.; Miranda, Rodolfo; Jelinek, Pavel; Feng, Xinliang; et al. (Angewandte Chemie International Edition, 2022)
The synthesis of long n-peri-acenes (n-PAs) is challenging as a result of their inherent open-shell radical character, which arises from the presence of parallel zigzag edges beyond a certain n value. They are considered as π-electron model systems to study magnetism in graphene nanostructures; being potential candidates in the fabrication of optoelectronic and spintronic devices. Here, we report the on-surface formation of the largest pristine member of the n-PA family, i.e. peri-heptacene (n=7, 7-PA), obtained on an Au(111) substrate under ultra-high vacuum conditions. Our high-resolution scanning tunneling microscopy investigations, complemented by theoretical simulations, provide insight into the chemical structure of this previously elusive compound. In addition, scanning tunneling spectroscopy reveals the antiferromagnetic open-shell singlet ground state of 7-PA, exhibiting singlet–triplet spin-flip inelastic excitations with an effective exchange coupling (Jeff) of 49 meV.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon Magnetism; Open-Shell Character; Periacenes; Scanning Tunneling Microscopy; Surface Chemistry